Competency Gaps and Workforce Readiness in the Era of Smart Ships: HRM Strategies for Developing Seafarer Capabilities in Automated and Digital Maritime Environments - Giovanni Battista Puteri (MANABIS: Jurnal Manajemen dan Bisnis, 2026)
The accelerating integration of automation, digitalization, and artificial intelligence into global shipping operations has created profound competency gaps within the maritime workforce, challenging traditional human resource management frameworks designed for conventional vessel operations. This study investigates the nature and scope of workforce readiness deficits created by smart ship technologies and examines the HRM strategies employed by global shipping companies to develop seafarer capabilities for automated and digital maritime environments. Using a qualitative research design with thematic analysis, thirty participants comprising maritime HR directors, seafarer training officers, maritime education specialists, and union representatives are interviewed across five major seafaring nations. Findings reveal critical competency gaps in digital navigation systems, remote monitoring operations, and cybersecurity awareness, alongside four strategic HRM responses encompassing competency-based training redesign, digital simulation integration, cross-functional crew development programs, and knowledge transfer systems. The study contributes to maritime HRM scholarship by providing a comprehensive framework for workforce capability development in the smart shipping era.